A frame-work development: Considering all aspect of human capital development (HCD) to achieve sustainability - Md. Tahzibul Haque; M. K. Wan Ibrahim; Ismail Maakip; Md. Abul Kalam Azad; Nazmina Chowdhury; Ahsan Habib; Khalilullah Muhammad Bayezid (TWIST Journal, 2025)
A thorough framework for human capital development (HCD) that incorporates social, emotional, cognitive, and physical aspects is presented in this research. It highlights the connections between job learning, health, formal education, and sociocultural flexibility. The concept emphasizes lifelong learning mechanisms, equitable resource access, competence upgrading, and impact assessment metrics, positioning human capital as both an input and an output of sustainable development processes. By redefining human capital as a transformative force for equity, resilience, and creativity, it places the framework within the framework of global development goals.